2013
DOI: 10.1186/1471-2164-14-115
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genomic sequence of Philosamia cynthia nucleopolyhedrin virus and comparison with Antheraea pernyinucleopolyhedrin virus

Abstract: BackgroundTwo species of wild silkworms, the Chinese oak silkworm (Antheraea pernyi) and the castor silkworm Philosamia cynthia ricini, can acquire a serious disease caused by Nucleopolyhedrin Viruses (NPVs) (known as AnpeNPV and PhcyNPV, respectively). The two viruses have similar polyhedral morphologies and their viral fragments share high sequence similarity. However, the physical maps of the viral genomes and cross-infectivity of the viruses are different. The genome sequences of two AnpeNPV isolates have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Furthermore, A. pernyi is now used as a model organism for a variety of research purposes because of the ease of its rearing and experimental manipulation compared with other lepidopteran insects. However, the health and vigor of A. pernyi are threatened by numerous parasites and pathogens, including viruses, mites, bacteria, and protozoans . In addition, the growth and development of larva are also strongly affected by environmental conditions, including heavy metal pollution, climate, foliage, and diseases …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, A. pernyi is now used as a model organism for a variety of research purposes because of the ease of its rearing and experimental manipulation compared with other lepidopteran insects. However, the health and vigor of A. pernyi are threatened by numerous parasites and pathogens, including viruses, mites, bacteria, and protozoans . In addition, the growth and development of larva are also strongly affected by environmental conditions, including heavy metal pollution, climate, foliage, and diseases …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies on A. pernyi have primarily focused on cloning and functional analysis of certain structural or stress‐related protein‐coding genes (Liu et al., 2014; Liu, Liu, et al., 2018; Liu, Xin, et al., 2018; Liu, Xin, et al., 2018; Liu, You, et al., 2014; Sezutsu & Yukuhiro, 2000; Yukuhiro, Kanda, & Tamura, 1997; Zhang et al., 2015), along with investigating its role in nucleopolyhedrovirus infection (Liu, Wang, et al., 2019; Qian et al., 2013; Sun et al., 2017; Wang, Na, Duan, et al., 2019; Wang, Na, & Qin, 2019; Zhang, Zhu, Dai, L. Liu, & Luo, 2016), and the nature of the silk fibre (Silva, Kundu, Lu, Reis, & Kundu, 2019; Suzuki, Chirila, & Edwards, 2016; Zhang, Yang, Shao, & Hu, 2010). These studies identified a few key genes, along with providing some insights into the characteristics of viral infection and the properties of natural silk.…”
Section: Introductionmentioning
confidence: 99%
“…The Eri-silkworm, Philosamia cynthia ricini, a wild silkworm belong to Saturniidae, Attacinae, Philosamia, cynthia, ricini, is native to the Assam Forest in northeastern India (Qian et al 2013), and was introduced into China for silk production in the 1950s (Liu et al 2010). It is a completely metamorphosed, without diapauses insect, and can be adapted to high temperature and high humidity environment.…”
mentioning
confidence: 99%